Competitive inhibition of bile acid synthesis by endogenous cholestanol and sitosterol in sitosterolemia with xanthomatosis. Effect on cholesterol 7 alpha-hydroxylase. - Shefer, S; Salen, G; Nguyen, L; Batta, A K; Packin, V; Tint, G S; Hauser, S (The Journal of Clinical Investigation, 1988)
The 7 alpha-hydroxylation of two cholesterol analogues, sitosterol and cholestanol, and their effect on the 7 alpha-hydroxylation of cholesterol were measured in rat and human hepatic microsomes. In untreated rat liver microsomes, the 7 alpha-hydroxylation of cholesterol was higher than that of cholestanol (1.4-fold) and sitosterol (30-fold). After removal of endogenous sterols from the microsomes by acetone treatment, the 7 alpha-hydroxylation of cholesterol was similar to that of cholestanol and only fourfold higher than that of sitosterol. Cholestanol and sitosterol competitively inhibited cholesterol 7 alpha-hydroxylase in both rat and human liver microsomes, with cholestanol the more potent inhibitor. Patients with sitosterolemia with xanthomatosis, who have elevated microsomal cholestanol and sitosterol, showed reduced cholesterol 7 alpha-hydroxylase activity relative to the activity in control subjects (13.9 and 14.7 vs. 20.3 +/- 0.9 pmol/nmol P-450 per min, P less than 0.01). Enzyme activity in these patients was 40% higher when measured in microsomes from which competing sterols had been removed. Ileal bypass surgery in one sitosterolemic patient decreased plasma cholestanol and sitosterol concentrations and resulted in a 30% increase in hepatic microsomal cholesterol 7 alpha-hydroxylase activity. Cholesterol 7 alpha-hydroxylase appears to have a specific apolar binding site for the side chain of cholesterol and is affected by the presence of cholestanol and sitosterol in the microsomal substrate pool. Reduced bile acid synthesis in sitosterolemia with xanthomatosis may be related to the inhibition of cholesterol 7 alpha-hydroxylase activity by endogenous cholesterol analogues.